Pelaksanaan Program Pengelolaan Penyakit Kronis PROLANIS pada Ibu Hamil Penyakit Diabetes Melitus di Puskesmas Bontomarannu Kabupaten Takalar - Suarni Suarni; Andi Nur Arifah Apriani Azis; Syauqiyah Awaliah Alfiani Nur; Muh Nasrun; Muh. Asrul Taufiq Arifuddin (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2026)
Diabetes mellitus prevalence has been increasing all over the world as in Indonesia. This chronic disease needs a continous and comprehensive management including medical and non medical intervension. In Indonesia since 2010 PT. Askes as the national health insurance company has developed prolanis (Chronic disease management program), a program to improve quality of dibetes mellitus management by general practitioners by providing training and set a monitoring system for diabetes treatment. Prolanis is approach to decrease complication and achieve highest quality of life with cost effective and rational healthcare. This study aims to determine the executive personnel, facilities and infrastructure, and operational expenses on program implementation prolanis in patients with diabetes mellitus in Bontomarannu Health Center, as well as knowing prolanis implementation process and the number of patients with diabetes mellitus who regularly follow prolanis club. The results showed that the implementation of prolanis still unfavorable, marked by lack of awareness of participants for the event prolanis seen from the low number of participants in the implementation prolanis presence. Based on the research results, it is suggested to Bontomarannu Health Center in order to increase attendance prolanis and health promotion of the dm to participants and maximize the implementation of gymnastics and education as well as To the City Health Office of Medan in order to further improve supervision of the implementation of the relevant health centers prolanis.